(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2016)
Gene therapy is strategy based on using genes as pharmaceuticals. Gene therapy is a treatment that involves altering the genes inside body's cells to stop disease. Genes contain DNA- the code controlling body form and function. Genes that do not work properly can cause disease. Gene therapy replaces a faulty gene or adds a new gene in an attempt to cure disease or improve the ability of the body to fight disease. Gene therapy holds promise for treating a wide range of diseases, including cancer, cystic fibrosis, heart disease, diabetes, hemophilia and AIDS. Various types of genetic material are used in gene therapy; double-stranded DNA (dsDNA), single-stranded DNA (ssDNA), plasmid DNA and antisense oligodeoxynucleotides (ASON). The success of gene therapy depends on assuring the entrance of the therapeutic gene to targeted cells without any form of biodegradation. Commonly used vectors in gene therapy are: adenoviruses (400 clinical studies; 23.8%), retroviruses (344 clinical studies; 20.5%), unenveloped/plasmid DNA (304 clinical studies, 17.7%), adeno-associated viruses (75 clinical studies; 4.5%) and others. In this paper, we have reviewed the major gene delivery vectors and recent improvements made in their design meant to overcome the issues that commonly arise with the use of gene therapy vectors.